DESCRIPTION OF MATHEMATICS PROBLEM SOLVING ABILITY IN TERMS OF LEARNING STYLE - Ahmad Aas Syamsuadi; A. Aspar; Andi Alim Syahri (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to describe and determine students' abilities to solve mathematical problems that focus on visual and auditory learning styles. Subjects are eighth-grade students from junior high school in Bulukumba district. This research is descriptive qualitative, which seeks to determine and describe the mathematical problem solving ability in terms of student learning styles. Data is collected using questionnaires, tests, and interviews. The use of questionnaires describes visual learning styles and auditory learning styles. Two numbers of the test determine mathematics problem solving ability in Polya's step, and interviews confirm mathematics problem solving ability. The data analysis techniques are reduction, presentation, and verification. Based on the results, the first subject with a visual learning style can fulfill all the indicators of Polya's steps, but another one is just three indicators. The first subject with an auditory learning style can meet all Polya's steps, but the other can fulfill three indicators.